2021
DOI: 10.3390/nano11020549
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of SiO2@Ag Mesoporous Nanoparticle Coating for Inhibition of Escherichia coli Bacteria on Various Surfaces

Abstract: Silver nanoparticles (Ag NPs) as antibacterial agents are of considerable interest owing to their simplicity, high surface area to volume ratio, and efficient oligodynamic properties. Hence, we investigated the synthesis of silica-supported Ag NPs (SiO2@Ag) as an effective antibacterial agent by using a wet-impregnation method. The formation of SiO2@Ag with Ag NP (5–15 nm diameter) on the silica particle (100–130 nm diameter) was confirmed with transmission electron microscopy (TEM). The study on antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…1B). 38 Meanwhile, the XRD patterns of 0.01Ag-NS-K-C and 0.1Ag-NS-K-C show peaks attributed to Ag metal 39 and a broad profile with kaolinite amorphization; 31,32 the former Ag peaks were more intense than the latter (Fig. 2A).…”
Section: Resultsmentioning
confidence: 97%
“…1B). 38 Meanwhile, the XRD patterns of 0.01Ag-NS-K-C and 0.1Ag-NS-K-C show peaks attributed to Ag metal 39 and a broad profile with kaolinite amorphization; 31,32 the former Ag peaks were more intense than the latter (Fig. 2A).…”
Section: Resultsmentioning
confidence: 97%
“…Acharya et al [ 90 ] demonstrated that Ag@SiO 2 core-shell nanoparticles (~17 nm) had a more substantial antibacterial effect on B. subtilis , S. aureus , Serratia marcescens, and K. pneumoniae than singular Ag NPs (~14 nm) due to controlled and sustainable release of Ag(I). Correspondingly, Gankhuyag et al [ 91 ] and Pal et al [ 92 ] recorded an enhanced bactericidal activity of SiO 2 @AgNPs and Ag-NP hybrid silica films against E. coli cells, respectively. A similar effect was reported for the core-shell silver–silica nanosystem against highly resistant Mycobacterium tuberculosis [ 93 ].…”
Section: Biological Studiesmentioning
confidence: 99%
“…AgNPs have been successfully loaded on various porous supports to enhance the antimicrobial efficiency; Yang et al described E. coli inactivation by AgNPs anchored on titania nanotubes [13], Joarder et al reported enhanced antibacterial activity of AgNPs deposited on MCM-41 type mesoporous silica [14], Guo et al described sustained release behavior of halloysite nanotubes loaded with the AgNPs [15], Dung et al fabricated silver-doped ceramic filter for antimicrobial water purification [16], and Chen et al reviewed the antibacterial activity of silver doped polymeric nanostructures [17]. However, it is necessary to achieve a proper antimicrobial coating that can be applied to a variety of substrates since bare or supported AgNPs could exhibit some adverse effects due to excessive leaching in moist environments that could lead to diminished antibacterial activity and make the environment toxic as well [18][19][20]. Antimicrobial coatings based on AgNPs have been used in medical implants, biomedical devices, and in packaging material to inhibit the bacterial infection [3,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%